Trajectory Planning of Robot based on the Jerk Optimal - Wang Wenjie; Qin Xiansheng; Wang Hongbo; Niu Junlong; Tan Xiaoqun; Zhang Xuefeng (Jixie chuandong)
According to the need of the stability and complexity of the robot trajectory path,a method of Cartesian space trajectory planning based on the Jerk optimal is presented,a smooth and stable robot motion trajectory is obtained. The trajectory path is imposed through limits on the waypoints in the Cartesian space,the continuous differentiable cosine curve is used to interpolate the robot trajectory path between the waypoints,and the expected joint angle of robot is calculated by solving the inverse kinematics. Finally,the trajectory planning method is validated through simulations and experiments on NAO robot. The experimental results show that the smoothness and stability of the trajectory path is excellent,the experiment task action are completed successfully.